De las stock options a las gifted actions - Chiriboga, Margoth (2024)
Historically, we have sought to reconcile the interests of workers and company owners, recognizing that the efforts of employees should be rewarded and motivated, as well as the vision of investors. We propose a mechanism where shares are awarded to outstanding workers based on their performance, subject to ongoing evaluations, with the possibility of recovery for non-compliance. Shareholders welcome these workers, but the shares are expected to be non-transferable and not part of a succession process, seeking to balance the needs of the workers with the protection of shareholder interests.